Exploring "Angry" and "Like" Reactions on Uncivil Facebook Comments That Correct Misinformation in the News. Issue 8 (14th September 2021) - Masullo, Gina M.; Kim, Jiwon
Abstract: This study examines the effect that uncivil news engagement comments that correct misinformation on a news story posted on Facebook have on newsreaders' perceptions and attitudes. This study also considers whether social reactions, such as a "like" or an "angry" posted on correcting comments, will influence newsreaders' perceptions and attitudes. Results from a survey experiment ( N  = 873) in the United States show that if comments that correct misinformation are uncivil, they led newsreaders to perceive the correcting comments and the commenters who posted them less favourably, although no effects on perceptions of the credibility of the news story itself were found. In addition, we found that uncivil correcting comments increased dislike for the political out-group in some instances unless they were marked with an "angry" social reaction. The "angry" reaction reversed the effect of the incivility, leading to decreased dislike for the out-group. Our findings advance digital journalism studies related to news engagement by showing the effects of incivility in corrections of misinformation and explaining how social reactions may alter the effect of these corrections.